Mix Methods for Ethnic Acculturation Study on History of Architectural Elements: Vernacular Houses during Pontianak Sultanate - Muhammad Hidayat; Budi Prayitno; Dwita Hadi Rahmi (Universitas Sebelas Maret Surakarta, 2020)
This study aims to find the embodiment of ethnic acculturation in the vernacular architectural elements of Pontianak's old houses showing multicultural culture in the past. The Pontianak community has been a multi-ethnic community from the start, with four dominant ethnic groups forming the Pontianak city, namely the Arab, Bugis, Banjar and Riau ethnic groups. The research used a qualitative-rationalistic method with the deeply observed in field case based on the mixed approach between the historical study of the role of each ethnic group and the typology study of architectural building elements. Research sample data in the form of Pontianak old houses are houses built between the early 19th century and the mid-20th century. The results of this study, firstly, the occurrence of ethnic acculturation on the elements of housing architecture in an integrated-assimilative manner. Secondly, the existence of the order of acculturation remained alive in traditional Pontianak community institutions until the mid-20th century shows a strong indication of the continuation of Vernacular Architecture discourse of the Pontianak Malay House.